(untitled) - Popper, Karl R. (London, 1968)
The Logic of Scientific Discovery (1934) The logic of scientific discovery. A survey of some fundamental problems. On the problem of a theory of scientific methods. Theories IV. Falsifiability V. The problem of the empirical basis. Degrees of testability. Simplicity. Probability. Some observations on quantum theory. Corroboration, or how a theory stands up to test.
Keywords: Science,Khoa học; Methodology,Phương pháp học